Non-melanoma skin cancer among ethnic German immigrants (resettler) from the former Soviet Union: a cohort study from 1990 to 2007 - Markeeva-Ilisevic, Evgenia; Holleczek, Bernd; Becher, Heiko; Winkler, Volker (Archives of public health, 2022)
UV radiation is a significant risk factor for non-melanoma skin cancer (NMSC). Ethnic Germans (resettlers) who immigrated to Germany from the former Soviet Union may have had a relatively high UV light exposure and thus a higher risk of developing NMSC. We compared the incidence of NMSC in a resettler cohort with the general population of the Saarland (Federal state of Germany) in relation to tumour location.
Gesehen am 18.05.2022